Penggunaan Media Sosial TikTok Produk The Originote Sebagai Komunikasi Pemasaran Online - Febriyanti, Yeni; Suryasuciramadhan, Arfian; Zulfikar, Meiby; Nurhasanah, Samsiah; Amalia, Dian Utami (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Social media plays an important role as a means for carrying out various communication activities, including marketing communications, where this platform provides the ability for brands to interact directly with their audience. Tiktok is a platform that plays a role in facilitating digital marketing. TikTok has recently received a lot of attention from social media users and has had a significant impact on the entrepreneurship industry. Tiktok has become an application that is popular with many individuals, which has given rise to various new business ideas. The Originote is one of the imported skincare brands that will enter the Indonesian market in 2022. This brand became very popular on TikTok social media when it first appeared in Indonesia, to be able to beat competitors who have survived longer. In conducting this research the author used a qualitative description method with data collection techniques through literature study. This method was chosen because of its ability to explore deep meaning and understanding of complex phenomena through diverse perspectives. The results of the research show that TikTok social media has an important role in the marketing communications process, by utilizing the features on TikTok and the role of influencers who can help influence consumer buying interest. This shows that the use of TikTok social media is an effective tool in carrying out marketing communications.